Real-world effectiveness of steroids in severe COVID-19: longer courses associated with lower risk of death or ICU admission - Wang,W; Snell,LB; Ferrari,D; Goodman,AL; Price,NM; Wolfe,CD; Curcin,V; Edgeworth,JD; Wang,Y (2022)
Abstract Purpose We aim to investigate the associations of steroid and length of steroid use with outcomes in severe COVID-19.Methods Severe cases of COVID-19, defined by hypoxia at presentation, and admitted to a multi-site healthcare institution in London were analysed between 02-Sep-2020 and 27-May-2021. The associations between duration of steroid treatment (prescription-days) and outcomes were explored using Cox proportional-hazards models adjusting for confounders. Length of steroid treatment was analysed as both a continuous variable and categorised into < 3, 3–10, and > 10 days. The primary outcome was in-hospital mortality and secondary outcome was in-hospital mortality or intensive care unit (ICU) level-3 admission.Results 734 severe COVID-19 cases were included, with 137/734 (18.7%) treated with steroids for < 3 days, 497/734 (67.7%) for 3–10 days, and 100/734 (13.6%) for > 10 days. Cox modelling with continuous days showed increasing length of steroids decreased the hazard of in-hospital mortality by a factor of 0.98 [95% CI: 0.96-1.0] per additional day and in-hospital mortality or ICU admission by a factor of 0.91 [95% CI: 0.87–0.95] per additional day. Further, when taking 3–10 days steroid treatment group as the reference group, > 10 days steroid showed trends towards decreased hazards for death (HR 0.59 [95%CI: 0.30–1.14]) and was significantly protective for death/ICU outcome (HR 0.28 [95%CI: 0.11–0.68]).Conclusion The protective effect of steroid for severe COVID-19 reported in randomised clinical trials was replicated in this large real-world cohort. We found an association between longer steroid courses and lower risk of death or ICU admission that warrants further investigation.